Phytochemical Screening and Pharmacological Activities of Echium judaeum Lacaita Extracts Growing Wild in Jordan - al- hamaideh, khawla; El-Elimat, Tamam; Afifi, Fatma; Kasabri, Violet (Jordan Journal of Pharmaceutical Sciences, 2021)
Echium judaeum Lac. (Boraginaceae) growing wild in Jordan has not been studied before phytochemically and pharmacologically. In this study the hydro-alcoholic extract was analyzed using Ultra Performance Liquid Chromatography-Mass Spectrometry (UPLC-MS). Total phenols and flavonoids were determined colorimetrically. Using SRB assay, the anti-proliferative effect against a panel of colorectal cancer cell lines (HT29, HCT116, SW620 and CACO2) was determined. Moreover anti- lipedimic and anti-obesity effects were examined, in addition to the determination of median lethal dose (LD50) of the aqueous extract. UPLC-MS analysis resulted in the identification of 6 compounds; luteolin, kaempferol, esculin, rosmarinic acid, echiumine and echimidine. LD50 was more than 3000mg/kg body weight. Neither anti-obesity nor anti-proliferative effects were detected. Since E. judaeum is a safe species and contains phenolic compounds, further pharmacological screening is recommended.